The Use of Card Sort Method to Improve Student Learning Activity in Islamic Education Learning at SMA Negeri 1 Simpang Kanan - Mawaddah (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve the learning activity of students on the material of emulating the role of Islamic scholars in Indonesia in class X of SMA Negeri 1 Simpang Kanan. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were high school students. The data for this study were obtained using a qualitative approach. The data analysis techniques used in this study were observation, interviews and documentation. The results of the study indicate that the use of the Card Sort method can improve the learning activity of students on the material of emulating the role of Islamic scholars in Indonesia in class X of SMA Negeri 1 Simpang Kanan. The results of observations in the field show that student learning activity has increased in each cycle. Overall, student learning activity from cycle I only reached 50% then increased in cycle II to 75% and then increased again in cycle III to 85%. Thus, the use of the card sort method to improve student learning activity on the material of emulating the role of Islamic scholars in Indonesia can be used as an alternative to improve student learning outcomes.